Wavelet packet transform-based compression for teleoperation. (August 2015) - Kuzu, Ahmet; Baran, Eray A; Bogosyan, Seta; Gokasan, Metin; Sabanovic, Asif
This paper introduces a codec scheme for compressing the control and feedback signals in networked control and teleoperation systems. The method makes use of Wavelet Packet Transform (WPT) and Inverse Wavelet Packet Transform (IWPT) for coding and decoding operations, respectively. Data compression is carried out in low-pass filter output by reducing the sampling rate, and in high-pass filter output by truncating the wavelet coefficients. The proposed codec works on both directions of signal transmission between a master robot and a slave robot over a networked motion control architecture. Following the formulation of the compression/decompression methodology, experimental validation is conducted on a single-degree-of-freedom motion control system. In the experiments, responses from different Wavelet structures are analyzed and a comparative study is carried out considering the factors of compression rate, reconstruction power error and real-time computational complexity. It is confirmed that the controller using the proposed compression algorithm performs very close to the uncompressed one while enabling transmission of much less data over the network.